Nanostructured 2D WS2@PANI nanohybrids for electrochemical energy storage - Crisci, Matteo; Boll, Felix; Merola, Leonardo; Pflug, Jonas Johannes; Liu, Zheming; Gallego, Jaime; Lamberti, Francesco; Gatti, Teresa (Frontiers in Chemistry, 2022)
2D materials are interesting flat nanoplatforms for the implementation of different electrochemical processes, due to the high surface area and tunable electronic properties. 2D transition metal dichalcogenides (TMDs) can be produced through convenient top-down liquid-phase exfoliation (LPE) methods and present capacitive behavior that can be exploited for energy storage applications. However, in their thermodynamically stable 2H crystalline phase, they present poor electrical conductivity, being this phase a purely semiconducting one. Combination with conducting polymers like polyaniline (PANI), into nanohybrids, can provide better properties for the scope. In this work, we report on the preparation of 2D WS2/PANI hybrid materials in which we exploit the LPE TMD nanoflakes as the scaffold onto which induce the in-situ aniline polymerization and thus achieve porous architectures with the help of surfactants and sodium chloride acting as templating agents. We characterize these species for their capacitive behavior in neutral pH, demonstrating the attractiveness of similar nanohybrids for future use in low-cost supercapacitor devices.